Green synthesis of NiO nanobelts with exceptional pseudo-capacitive properties - Wang, Bao (2013)
NiO nanobelts are prepared by a simple, green method. The as-prepared NiO nanobelts have supercapacitive performance that is superior to other NiO-based electrode materials, with a very high specific capacitance of ≈600 F g^−1 at a high current density of 5 A g^−1, 94% of which is retained after 2000 cycles.